Upper respiratory tract infection: drug utilization study - Naik, Harish; Kolur, Ashwini (International Journal of Basic & Clinical Pharmacology, 2017)
Background: One of the most common causes of visit to physician is upper respiratory tract infections (URTI). This infection is often considered to be of little value from a stand point of mortality but this infection is responsible for limited activity and absence from work and school in the general population of nation mainly in a developing country like India, when compared it with other infections. Methods: This study was conducted in Krishna Institute of Medical Sciences, Karad, India to see the prescription pattern of URTI patients in medicine department. It was a retrospective study record based, observational study and the data were collected from the medical record room. Results: Out of 212 patients, 53.30% were of URTI, 31.60% were sinusitis, pharyngitis and CSOM accounted for 11.79% and 3.30% respectively. Female accounted for 62.26% and male for 37.73% of total cases. In 8 cases culture and sensitivity was done and all were sterile. Only in 8 cases antimicrobial agents were not prescribed. Conclusions: Azithromycin was the most commonly used antimicrobial, followed by ceftriaxone. Apart from antibiotics the most frequently prescribed class was antihistamines followed by expectorants and bronchodilators. Paracetamol was the preferred antipyretic. Acid reducing agents were prescribed in 84.82% of Patients, might be used to check the acidity caused by antibiotics. The use of generic medicines should be promoted.